Comparing Deep Breathing and Semi-Fowler Position to Reduce Respiratory Rate in Asthma Patients: A Quasi-Experimental Study - Oktorina, Rola; Oktavia, Minda; Wahyuni, Aria; Rahman, Waldi; Yenni, Yenni; Rofi’i, Aby Yazid Al Busthomy (REAL in Nursing Journal, 2025)
Background: Asthma remains a global health burden, marked by recurrent respiratory symptoms that significantly affect quality of life. Non-pharmacological nursing interventions such as deep breathing and semi-Fowler positioning have been increasingly recommended to improve respiratory function in patients with asthma. However, few studies have compared the relative effectiveness of these two interventions within a single experimental framework. Purpose: This study aimed to compare the effectiveness of deep breathing exercises and the semi-Fowler position in reducing respiratory rate among asthma patients. Methods: A quasi-experimental study was conducted involving 70 asthma patients, divided into two intervention groups: deep breathing (n = 35) and semi-Fowler position (n = 35). Participants were recruited using purposive sampling based on defined inclusion and exclusion criteria. Data on respiratory rate were collected before and after intervention using direct observation, recorded in breaths per minute. Paired and independent t-tests were used for statistical analysis with a significance level of α < 0.05.Result: In the deep breathing group, the mean respiratory rate decreased significantly from 29.03 ± 2.20 to 18.29 ± 1.56 breaths/minute (mean difference = 10.74; p < 0.001). Similarly, in the semi-Fowler group, the respiratory rate reduced from 28.43 ± 1.98 to 18.29 ± 1.66 breaths/minute (mean difference = 10.14; p < 0.001). However, the post-intervention comparison between the two groups showed no statistically significant difference (p = 1.00).Conclusion: Both deep breathing and semi-Fowler positioning are effective in reducing respiratory rate among asthma patients. These findings suggest that nurses can apply either method based on patient preference and clinical context, supporting individualized, evidence-based respiratory care.